The Great Deceiver: A Case of Central Sensitization Presenting as Carcinoid Syndrome. Issue 11 (1st June 2016) - Ramos, Juan A.
Abstract : Central sensitization defines a state of amplified sensory input within the nervous system across many organ systems; it overlaps syndromes as fibromyalgia, chronic fatigue, irritable bowel, and interstitial cystitis. Commonly, individuals will experience multiple syndromes during the course of their lifetime. A 62-year-old patient presented for evaluation of multiple medically unexplained symptoms postsurgically including chronic left chest wall and flank pain with concomitant diarrhea, abdominal pain, and facial flushing. After extensive multidisciplinary evaluations, he was diagnosed as having central sensitization in which the initial presentation mimicked carcinoid syndrome. He was subsequently treated with extensive multidisciplinary pain rehabilitation, and it did well.